Revolusi Dunia Bisnis Indonesia Melalui E-Commerce dan E-Business: Bagaimana Solusi Hukumnya - Nindyo Pramono (Fakultas Hukum Universitas Islam Indonesia, 2001)
The activities of electronic trade have brought about revolution in the business world, suchas the emergence of e-commerce and e-business. Yet, the impact of such activities have resulted in various legal problems. This writing tries to explore some growingproblems and solutions being of fered from the impact of e-commerce and e-business development.